2021
DOI: 10.3390/biology10060482
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Composition on Physical Literacy in Spanish Children

Abstract: Background: Childhood obesity is a major health challenge in modern societies; therefore, prevention and management policies are needed. This study aims to establish the level of Physical Literacy (PL) in overweight and non-overweight children in Extremadura (Spain), analysing the potential differences between them and exploring their relationships with body composition. Methods: A single-measure cross-sectional study was performed with 135 children, who were taken anthropometric measurements and administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
2
25
1
Order By: Relevance
“…Regarding level of PL, several studies have provided results in schoolchildren from different countries [ 54 , 55 , 56 , 57 , 58 ] based on CAPL-2. Most reported worrying results since more than 50% of the schoolchildren participating in these studies did not achieve sufficient PL [ 54 , 55 , 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding level of PL, several studies have provided results in schoolchildren from different countries [ 54 , 55 , 56 , 57 , 58 ] based on CAPL-2. Most reported worrying results since more than 50% of the schoolchildren participating in these studies did not achieve sufficient PL [ 54 , 55 , 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that “motivation and confidence” and “physical competence” domains are the CAPL domains with the strongest correlation [ 60 ]. Specifically, recent studies found that the greater the percentage of schoolchildren in the domain “motivation and confidence”, the greater the percentage for “physical competence” [ 57 , 58 ]. Other studies have shown that physically active students scored higher on autonomous motivation than non-active students [ 61 , 62 ] and that students who satisfied the needs for autonomy, competence and relatedness were more likely to participate in PE-related activities for self-determined reasons and were less likely to feel demotivated [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, physically inactive youth are more likely to be overweight (29), and the physical literacy ( i.e. , competence, confidence, and motivation to participate in physical activity) of overweight children tends to be lower than normal weight youth (30). Additionally, overweight youth tend to experience greater parent distress and peer victimization, which are associated with a lower quality of life (31).…”
Section: Youth Physical Inactivity and Ill-mental Healthmentioning
confidence: 99%